2022
DOI: 10.3389/fpubh.2022.900077
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and Spatiotemporal Arboviruses Forecasting by Machine Learning: A Systematic Review

Abstract: Arboviruses are a group of diseases that are transmitted by an arthropod vector. Since they are part of the Neglected Tropical Diseases that pose several public health challenges for countries around the world. The arboviruses' dynamics are governed by a combination of climatic, environmental, and human mobility factors. Arboviruses prediction models can be a support tool for decision-making by public health agents. In this study, we propose a systematic literature review to identify arboviruses prediction mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 115 publications
0
2
0
Order By: Relevance
“…Due to its inherent capability to perform prediction tasks, ML techniques have been increasingly utilized in the study of diseases in populations, being successfully employed in public health research, with notable examples being found in the study of air pollution 23 , arboviruses 24 , COVID-19 25 and TB 26 . Similarly, we employed ML models to better understand the most influential TB surveillance variables in the incidence of disease in the region.…”
Section: Discussionmentioning
confidence: 99%
“…Due to its inherent capability to perform prediction tasks, ML techniques have been increasingly utilized in the study of diseases in populations, being successfully employed in public health research, with notable examples being found in the study of air pollution 23 , arboviruses 24 , COVID-19 25 and TB 26 . Similarly, we employed ML models to better understand the most influential TB surveillance variables in the incidence of disease in the region.…”
Section: Discussionmentioning
confidence: 99%
“…Previous systematic reviews have been conducted to identify and characterise dengue transmission models focused on predicting trends over time (hindcasting with the goal of developing forecasting systems) as opposed to spatially explicit prediction (risk mapping) [15][16][17]. Some of these systematic reviews included risk mapping studies but they have been limited to just a single arbovirus, usually dengue [7,[18][19][20].…”
Section: Introductionmentioning
confidence: 99%